Stages and prospects for the development of information technologies in medicine (Multidisciplinary Journal of Science and Technology, 2026)
The development of information technologies (IT) in medicine has transformed healthcare delivery from paper-based systems to advanced digital ecosystems. This article examines the historical stages of IT adoption in medicine, including early digitization, integration of electronic health records (EHR), and the current era dominated by artificial intelligence (AI), telemedicine, Internet of Medical Things (IoMT), and blockchain. Future prospects for 2026 and beyond highlight trends such as 5G-enabled real-time monitoring, quantum computing for drug discovery, and personalized precision medicine. Special attention is given to Uzbekistan's progress in digital health reforms, including the implementation of unified platforms like DMED and telemedicine initiatives. IT enhances diagnostic accuracy, patient access, and operational efficiency while addressing challenges like cybersecurity and interoperability.